Encuentros imposibles. Montajes anacrónicos en las obras de hijos de desaparecidos argentinos (Altre Modernità, 2022)
The aim of this contribution is to analyse a corpus of three essays by photographers belonging to the generation of Argentinean HIJOS – Arqueología de la ausencia (2001) by Lucila Quieto, Recuerdos inventados (2003) by Gabriela Bettini and El viaje de papá (2005) by Camilo Del Cerro – whose common feature is the work that the photographers do with images of their parents combined with portraits of themselves. The critical-theoretical proposal to be advanced is that the three essays inaugurate a peculiar representational paradigm – that of the ‘anachronistic montage’, postulated on the basis of the theoretical proposals of Didi-Huberman, Benjamin and Agamben – capable of accounting for the modalities through which the impossible encounter between fathers and sons takes shape, and postulated in the light of a review of the pre-existing critical literature on the corpus, which illuminates the lack of a framework capable of accounting for two central characteristics of the works: the ambiguous temporal status and the functioning of montage as a representational technique, but also as an epistemological tool. Finally, to account for the critical potential of the proposal beyond the field of photography, two cases of application of the paradigm are presented in the analysis of two narrative works: Diario de una princesa montonera (2012) by Mariana Eva Perez and Magdalufi (2018) by Verónica Sánchez Viamonte.
Keywords: Argentine hijos; post-dictatorship Argentine photography; montage; anachronism; hijos’ literature